A key tool for identifying and managing the hidden potential of the family - Polyekhina, Anna (Global Prosperity, 2025)
Abstract. The article is devoted to the development of a key tool for identifying and managing family potential using the “1+1=100” method based on the experience of applying the FAIR principles. The purpose of the article is to provide a structural overview of the author’s model of building a stable family “1+1=100”, which is built on self-development and harmonization. The results of the study show that a family built on the basis of conscious interaction is not only a source of emotional support, but also a powerful platform for personal and spiritual growth. Within the framework of Anna Polyekhina’s author’s theory “1 plus 1 to level 100”, a structural model of a conscious family has been developed, consisting of three interconnected levels: “I”, “you”, “we”. The first level – “I” – represents deep self-awareness, spiritual integrity and integration of the personality, the formation of which is based on the concepts of phenomenology, existentialism and humanistic psychology. The second level – “you” – focuses on the perception of another person as an autonomous, free, self-sufficient individual who has the right to self-determination and development. The third level – “we” – conceptualizes the family as a space of interpersonal synergy, in which the integration of personal resources creates a new quality of interaction that significantly exceeds the individual capabilities of each person. The methodology is based on the principles of self-determination, dialogical interaction (according to Buber), humanistic acceptance (according to Rogers), as well as the philosophical understanding of the self as an integral spiritual center (according to Poll & Smith, Oberg). The key values of a conscious family are identified: awareness, respect for autonomy, emotional openness, spiritual maturity, partner support, purposefulness and collective responsibility. The practical significance of the study lies in the creation of a scientifically based concept that can be used in psychological counseling, educational programs for families and the formation of family policy strategies.